How do muscle lesions such as latent and active trigger points influence central nociceptive neurons? - Mense, Siegfried (Journal of musculoskeletal pain, 2010)
Objectives: This article aims at explaining some of the features of active and latent trigger points [TrPs], namely spontaneous pain, allodynia/hyperalgesia, and referral of pain.Findings: Spontaneous pain is mainly due to ongoing activity in nociceptive neurons in the spinal cord. Allodynia and hyperalgesia can be explained by a sensitization of central nociceptive neurons [central sensitization]. One mechanism of central sensitization is the release of substance P together with glutamate from presynaptic terminals of nociceptive fibers from muscle. Other steps of sensitization are the opening of N-methyl-d-aspartate channels on postsynaptic neurons and the de novo synthesis of ion channels.The current concept of pain referral assumes that the efficacy of synaptic connections of central dorsal horn neurons can change under the influence of a nociceptive input. Thus, ineffective synaptic connections can become effective. Pain referral appears to reflect the formation of new effective central nervous connections.One important characteristic of a latent TrP is that it does not elicit spontaneous pain but evokes referred pain. Pain referral from a latent TrP is probably due to the fact that the latent TrP has only ineffective connections with the central nervous system and that these synapses are located on neurons that supply regions remote from the TrP.Conclusions: Myofascial TrPs are not merely a peripheral phenomenon, the input from TrPs leads to hyperexcitability of central neurons that manifests itself in allodynia, hyperalgesia, and pain referral. These central changes are mainly based on an increase in the synaptic efficacy of central connections induced by nociceptive input.